SPEAKING PERFORMANCE AND GRAMMATICAL COMPETENCE ACROSS COGNITIVE LEARNING STYLES AND STRATEGY INVENTORY FOR LANGUAGE LEARNING (SILL) - Ayu Chandra Agustin; Ekaning Dewanti Laksmi; Suharyadi Suharyadi (Jurnal Pendidikan Humaniora, 2021)
Abstract: The correlation between speaking performance and grammatical competence has been a debatable issue. It is also believed that cognitive learning styles and learning strategies are two of the many factors that influence students' language achievement. This study aims to see the relationship between the argumentative speaking score variable and the multiple choice grammar test on 30 students of Economics at STIE Malangkuceswara. The results showed that there was no significant correlation between speaking performance and grammatical competence between cognitive learning styles and the Strategy Inventory for Language Learning (SILL). However in small differences, independent field students (FI) outperformed in speaking, whereas field-dependent students (FD) outperformed grammar competencies. Additionally, the study found that the students who scored higher on either the speaking or grammar tests used cognitive and meta-cognitive strategies more often than those who scored lower.Keywords: speaking performance, grammatical competence, cognitive learning style, field independent, field dependent, strategy inventory for language learning (sill)Abstrak: Korelasi antara kecakapan berbicara dan kemampuan bertata bahasa telah menjadi masalah yang masih diperdebatkan. Gaya belajar kognitif dan strategi belajar diyakini sebagai dua dari banyak faktor yang mempengaruhi nilai bahasa siswa. Penelitian ini bertujuan untuk melihat hubungan antara nilai tes kecakapan berbicara argumentatif dan nilai tata bahasa dalam tes pilihan ganda yang didapatkan dari 30 mahasiswa Ilmu Ekonomi STIE Malangkuceswara. Hasil penelitian menunjukkan tidak ditemukannya korelasi yang signifikan antara kecakapan berbicara dan kemampuan tata bahasa bedasarkan gaya belajar kognitif dan Strategy Inventory for Language Learning (SILL). Namun, terdapat perbedaan kecil dimana mahasiswa yang cenderung Field Independent (FI) unggul dalam berbicara, sedangkan mereka yang cenderung Field Dependent (FD) lebih unggul dalam tata bahasa. Selain itu, penelitian ini menemukan bahwa mereka yang mendapat nilai lebih tinggi baik dalam tes berbicara atau tata bahasa telah menggunakan strategi kognitif dan meta-kognitif lebih sering daripada yang mendapat nilai lebih rendah. Kata kunci: kecakapan berbicara, kemampuan tata bahasa, gaya belajar kognitif, field independent, field dependent, strategy inventory for language learning (sill)